2015
DOI: 10.1126/scitranslmed.aac8155
|View full text |Cite
|
Sign up to set email alerts
|

IL-2Rα mediates temporal regulation of IL-2 signaling and enhances immunotherapy

Abstract: IL-2 is a lymphocyte growth factor that is an important component of many immune-based cancer therapies. The efficacy of IL-2 is thought to be limited by the expansion of T regulatory cells, which express the high affinity IL-2 receptor subunit, IL-2Rα. IL-15 is under investigation as an alternative to IL-2. Although both cytokines signal through IL-2Rβγ, IL-15 does not bind IL-2Rα and therefore induces less T regulatory cell expansion. However, we found that transferred effector CD8+ T cells induced curative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…While the conventional signaling functions of the IL2Rγ-chain cytokine receptors are mediated by IL2Rβ, IL2Rγ, and IL7Rα [12], IL15Rα contributes by mediating trans-presentation and both IL2Rα and IL15Rα contribute by increasing the affinity and duration of interactions between IL2Rγ-chain cytokines and their receptors [1113,29,30]. In assessing the importance of the IL2Rα and IL15Rα subunits in IL-2- and IL-15-mediated proliferation of Th17 cells, we found that monoclonal antibody (PC61) blockade of IL2Rα had minimal effect on IL-2-mediated proliferation (supplementary figure 4b), with IL-2 still stimulating proliferation at significantly lower doses than IL-15.…”
Section: Resultsmentioning
confidence: 99%
“…While the conventional signaling functions of the IL2Rγ-chain cytokine receptors are mediated by IL2Rβ, IL2Rγ, and IL7Rα [12], IL15Rα contributes by mediating trans-presentation and both IL2Rα and IL15Rα contribute by increasing the affinity and duration of interactions between IL2Rγ-chain cytokines and their receptors [1113,29,30]. In assessing the importance of the IL2Rα and IL15Rα subunits in IL-2- and IL-15-mediated proliferation of Th17 cells, we found that monoclonal antibody (PC61) blockade of IL2Rα had minimal effect on IL-2-mediated proliferation (supplementary figure 4b), with IL-2 still stimulating proliferation at significantly lower doses than IL-15.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our study confirmed previous findings that lymphopenia is not a prerequisite for effective ACT (46). Several other approaches to improve ACT outcomes in the absence of irradiation and chemotherapy have been recently explored, including the use of antibodies for specific cell type depletion (46), genetically engineered tumor-specific T cells (47), Toll-like receptor (TLR) ligands (48) and other γ-chain cytokines (46,49). One foreseeable advantage of the regimen proposed in this study is the absence of CD4 + T cell ablation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that CD25 recycling participates in IL-2-mediated signaling (47,48) and that DOCK8 is also involved in cytoskeletal reorganization (49,50). The defect in IL-2 signaling observed in DOCK8-deficient Tregs could in part be due to abnormal CD25 recycling.…”
Section: Discussionmentioning
confidence: 99%